Effect of Ultrasonic Surface Rolling Process on Surface Properties and Microstructure of 6061 Aluminum Alloy - Xiquan Ma; Weihai Zhang; Shubo Xu; Kangwei Sun; Xinzhi Hu; Guocheng Ren; Jianing Li; Xianhua Zhao; Fei Gao (Materials Research, 2023)
Nano-surface layers were prepared on the surface of 6061 aluminum alloy using the ultrasonic surface rolling process (USRP). The surface morphology, surface roughness, microstructure, hardness, and corrosion resistance of 6061 aluminum alloy were systematically characterized using X-ray diffraction (XRD), laser scanning confocal microscopy (LSCM), optical microscope(OM), scanning electron microscopy (SEM), energy dispersive spectrometer (EDS), and other testing methods. The results showed that ultrasonic surface rolling strengthening did not change the surface phase composition of 6061 aluminum alloy. It changed the size of the surface phases and the distance between the phases while refining the surface grains. The static pressures has a great influence on the surface properties of 6061 aluminum alloy. The best surface properties were obtained under 500N static pressures. The surface hardness reached 129.5HV0.5, the surface morphology was flat and continuous, the surface roughness was reduced to Ra0.191μm, and the corrosion resistance was significantly improved.